Application of cervical collars: an analysis of practical skills of professional emergency medical care providers - Kreinest, Michael; Goller, Sarah; Rauch, Geraldine; Frank, Christian; Gliwitzky, Bernhard; Wölfl, Christoph Georg; Matschke, Stefan; Münzberg, Matthias (PLOS ONE, 2015)
The application of a cervical collar is a standard procedure in trauma patients in emergency medicine. It is often observed that cervical collars are applied incorrectly, resulting in reduced immobilization of the cervical spine. The objective of this study was to analyze the practical skills of trained professional rescue personnel concerning the application of cervical collars.
Gesehen am 24.07.2020